Caracterização de látices acrílicos em função da neutralização de seus grupos carboxilas - Santos, Zilvam Melo dos (2007)
Latexes based on acrylic acid, acrylamide, ethyl methacrylate, and ethyl acrylate were synthesized via emulsion polymerization with different monomer compositions. The resultant latices were thickened with different molar ratios of NaOH to acrylic acid and were analyzed in terms of acid‐basis titrimetry, turbidimetry, rheology, and tensiometry. Titrimetry, turbidimetry, and rheometry were used to analyze factors such as carboxyl group availability and particle solubilization, tensiometry monitoring the influence of carboxyl neutralization on polymer‐surfactant interactions. For the acrylic acid content used in this work (20 wt%), the results indicated that as carboxyl groups distribution became more homogeneous, the process of latex thickening became more effective